Performance progression of youth and Junior triathletes racing world triathlon sprint and super sprint races - Correa, G. S.; Rathbone, E.; Lorimer, A.; Eastwood, A.; Keogh, J. (Journal of Sports Sciences, 2026)
Europe stages highly competitive World Triathlon Youth and Junior competitions. Results from 46 sprint and super sprint European triathlon events between 2021 and 2023 included 2137 competition data entries of 494 males and 1576 entries of 351 females. The competition split-times were converted to average velocity to account for competition distance variability. Performance trajectories were estimated using linear mixed model regression and subdivided by sex, competition distance, and segment with age as the main factor of interest. Random effects included competition`s external factors, intra-athlete variability, and country of origin. Estimated velocity was not statistically different between sprint and super sprint distances in female swim, and male and female cycle, run, and full-race. Males were faster than females in all segments and across all ages. The total estimated performance progression from 15 to 19 years-of-age was small for adolescent triathletes: males (swimming ~4.2%; cycling ~3.2%; running ~6.0%); females (swimming ~2.4%; cycling ~1.7%; running ~4.1%). Age explained <7.0% of performance progression. Performance variance explained by random effects differed by sex, distance and segment. Despite the small contribution of age, the most successful adolescent triathletes continually develop at rates determined by sex.